PREVALENCE AND PREVENTIVE MEASURES FOR THALASSAEMIA IN HAZARA REGION OF N.W.F.P., PAKISTAN - Burki, Mumtaz Khan; Qayum, Iftikhar; Siddiqui, Noaman (Journal of Ayub Medical College Abbottabad, 1998)
65 cases of thalassaemia major were selected out of 300 cases of anaemia(21.667c) admitted to Paediatric Unit A in Women and Children Hospital, Abbottabad since June 1995, based on their family history clinical data, laboratory investigations and X-ray analyses. Most of them were between 1-5 years of age. No difference was noted between the two sexes. Parental consanguinity was present in 49.237c of cases and non-consanguinity in 24.617c, whereas data was not available in 26.157c. of cases. All the patients had moderate to severe anaemia and failure to thrive as their presenting symptoms. Other predominant associated features were splenomegaly(907c), typical facies (607c), skull changes on X-rays(607c), hepatomegaly (45%), jaundice(107c) and repeated infections such as gastroenteritis, pneumonia, etc. Some of them, particularly older children having received multiple blood transfusions, presented with complications such as viral hepatitis, congestive cardiac failure (4.617c) and diabetic ketoacidosis (1.537c). A variety of problems were encountered in diagnosis and management of these cases and are listed with suggested improvements in patient care.